HUBUNGAN IDENTITAS NASIONAL DENGAN POLA AKULTURASI REMAJA ETNIS TIONGHOA DI JAKARTA (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2022)
Ethnic Chinese are one of the minority groups in Indonesia who often receive discriminatory treatment. However, despite receiving continuous discrimination, the Chinese still "survive" and acculturate with other ethnic groups. The acculturation pattern has four categories (a) integration (sense of belonging to the original culture and current culture is high); (b) assimilation (sense of belonging to low native culture and high current culture); (c) separation (sense of belonging to high native culture and low current culture); (d) marginalization (sense of belonging to the original culture and current culture are all low) (Berry & Hou, 2016). This study aims to highlight the pattern of Chinese ethnic acculturation in Jakarta. The research method used is correlational quantitative method. The subjects are students at one of the universities in Jakarta, with the selection of samples using a convenience sampling technique. Data was collected using Google forms with 15-20 minutes to complete. Subjects who recognized themselves as ethnic Chinese totaled 115 people out of 277 submitted answers. The results of the study show that the national identity of all participants has a high value, meaning that the participants of this study have a national identity that does not need to be doubted. This can also be seen from each dimension that supports the national identity variable, as well as the acculturation variable which tends to be high in value. In the grouping of acculturation patterns, the most chosen is integration, which means that participants value the new culture highly, in this case, Indonesian culture and also highly value the original culture, in this case, the Chinese ethnic culture.